Self-assembling peptide matrix for the prevention of esophageal stricture after endoscopic resection: a randomized controlled trial in a porcine model. Issue 5 (29th March 2017) - Barret, M.; Bordaçahar, B.; Beuvon, F.; Terris, B.; Camus, M.; Coriat, R.; Chaussade, S.; Batteux, F.; Prat, F.
SUMMARY: Esophageal stricture formation after extensive endoscopic resection remains a major limitation of endoscopic therapy for early esophageal neoplasia. This study assessed a recently developed self-assembling peptide (SAP) matrix as a wound dressing after endoscopic resection for the prevention of esophageal stricture. Ten pigs were randomly assigned to the SAP or the control group after undergoing a 5-cm-long circumferential endoscopic submucosal dissection of the lower esophagus. Esophageal diameter on endoscopy and esophagogram, weight variation, and histological measurements of fibrosis, granulation tissue, and neoepithelium were assessed in each animal. The rate of esophageal stricture at day 14 was 40% in the SAP-treated group versus 100% in the control group ( P = 0.2). Median interquartile range (IQR) esophageal diameter at day 14 was 8 mm (2.5–9) in the SAP-treated group versus 4 mm (3–4) in the control group ( P = 0.13). The median (IQR) stricture indexes on esophagograms at day 14 were 0.32 (0.14–0.48) and 0.26 (0.14–0.33) in the SAP-treated and control groups, respectively ( P = 0.42). Median (IQR) weight variation during the study was +0.2 (−7.4; +1.8) and −3.8 (−5.4; +0.6) in the SAP-treated and control groups, respectively ( P = 0.9). Fibrosis, granulation tissue, and neoepithelium were not significantly different between the groups. The application of SAP matrix on esophageal wounds after a circumferential endoscopic submucosal dissection delayed the onset of esophageal stricture in a porcine model.